Oligometastatic NSCLC: Current Perspectives and Future Challenges - Sara Torresan; Jacopo Costa; Carol Zanchetta; Lorenzo De Marchi; Simona Rizzato; Francesco Cortiula (Current Oncology)
Oligometastatic non-small cell lung cancer (NSCLC) represents a separate entity with a different biology and prognosis compared to stage IV NSCLC. Challenges range from the very definition of oligometastatic disease to the timing and techniques of local treatments, and their benefit in prolonging patient survival. Most of the international consensus and guidelines agree on the need for shared criteria, such as appropriate stadiation and even tissue biopsy if needed, in order to select patients that could really benefit from personalised strategies. Multidisciplinary evaluation is crucial in order to define if every lesion is amenable to radical local treatment, which appears to be the most important criterion across different guidelines. A distinction must be made depending on the time of oligo-disease detection, separating de novo oligometastatic disease from oligorecurrence, oligoprogression and oligoresidual disease. These separate entities imply a different biology and prognosis, and treatment strategies consequently must be tailored. Locoregional approaches are therefore often contemplated in order to ensure the best outcome for the patient. In non-oncogene-addicted disease, the advent of immune checkpoint blockers (ICBs) allows physicians to take into consideration consolidative treatments, but timing, technique and subsequent systemic treatment remain open issues. In oncogene-addicted NSCLC, local treatments are nowadays preferably reserved to cases of oligoprogression, but the advent of new, more potent drugs might challenge that. In this review, we summarised the current knowledge, consensuses and data from retrospective and prospective trials, with the aim of shedding some light on the topic and emphasising the unmet clinical need.